Ligands for Melanocortin Receptors: Beyond Melanocyte-Stimulating Hormones and Adrenocorticotropin - Xiao-Chen Yuan; Ya-Xiong Tao (Biomolecules, 2022)
The discovery of melanocortins in 1916 has resulted in more than 100 years of research focused on these peptides. Extensive studies have elucidated well-established functions of melanocortins mediated by cell surface receptors, including MSHR (melanocyte-stimulating hormone receptor) and ACTHR (adrenocorticotropin receptor). Subsequently, three additional melanocortin receptors (MCRs) were identified. Among these five MCRs, MC3R and MC4R are expressed primarily in the central nervous system, and are therefore referred to as the neural MCRs. Since the central melanocortin system plays important roles in regulating energy homeostasis, targeting neural MCRs is emerging as a therapeutic approach for treating metabolic conditions such as obesity and cachexia. Early efforts modifying endogenous ligands resulted in the development of many potent and selective ligands. This review focuses on the ligands for neural MCRs, including classical ligands (MSH and agouti-related peptide), nonclassical ligands (lipocalin 2, β-defensin, small molecules, and pharmacoperones), and clinically approved ligands (ACTH, setmelanotide, bremelanotide, and several repurposed drugs).